2023
DOI: 10.1126/scitranslmed.abq2395
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a signaling modality within the gp130 receptor enhances tissue regeneration and mitigates osteoarthritis

Abstract: Adult mammals are incapable of multitissue regeneration, and augmentation of this potential may shift current therapeutic paradigms. We found that a common co-receptor of interleukin 6 (IL-6) cytokines, glycoprotein 130 (gp130), serves as a major nexus integrating various context-specific signaling inputs to either promote regenerative outcomes or aggravate disease progression. Via genetic and pharmacological experiments in vitro and in vivo, we demonstrated that a signaling tyrosine 814 (Y814) within gp130 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…However, our findings demonstrated that addition of exogenous rhGDF-15 does not promote spreading of the senescent phenotype, but, on the contrary, induced proliferation, migration, and cell survival of hAC. Similar results were currently reported in case of IL-6, which is a common SASP factor and controversially discussed in cartilage degeneration and regeneration [34][35][36]. Overall, it is widely accepted that transient senescence contributes to tissue regeneration and that SASP factors initially accelerate related processes, such as immune and stem cell recruitment, fibroblast activation, and ECM remodeling [37].…”
Section: Discussionsupporting
confidence: 79%
“…However, our findings demonstrated that addition of exogenous rhGDF-15 does not promote spreading of the senescent phenotype, but, on the contrary, induced proliferation, migration, and cell survival of hAC. Similar results were currently reported in case of IL-6, which is a common SASP factor and controversially discussed in cartilage degeneration and regeneration [34][35][36]. Overall, it is widely accepted that transient senescence contributes to tissue regeneration and that SASP factors initially accelerate related processes, such as immune and stem cell recruitment, fibroblast activation, and ECM remodeling [37].…”
Section: Discussionsupporting
confidence: 79%
“…The finding that signaling redoxosomes containing NOX2 and SRC were found in increased amounts in human osteoarthritic cartilage, especially at sites of damaged matrix, supports a role for redox regulation of SRC in OA. The importance of SRC in OA is supported by previous studies demonstrating that SRC inhibition reduces OA severity in preclinical animal models (44)(45)(46)48).…”
Section: Discussionmentioning
confidence: 75%
“…Stimulation of the chondrocyte α5β1 integrin by FN7-10 activates mitogen-activated protein kinase (MAPK) signaling, as well as signaling by the redox-regulated kinase SRC, resulting in the production of multiple matrix metalloproteinases (MMPs) and proinflammatory mediators involved in OA (39,40). Here, we focused on MMP-13 production as a general measure of catabolic integrin signaling given its prominent role in OA (19,41,42) and examined MAPK and SRC activation because they are required for FN7-10 stimulation of MMP-13 production (39,40,43) and can contribute to OA pathology (44)(45)(46)(47)(48).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of mutant mice on HFD had mild or minimal symptoms of OA, while WT counterparts developed mild to severe OA (Figure 2F). SFK activation is reported to be critical for cartilage degeneration in OA, and our group has demonstrated that F814 cartilage explants were resistant to OSM-induced degeneration (18,33). Mild synovitis, a characteristic of OA induced by low-grade chronic inflammation, was present in the majority of mice in both WT and F814 groups, although F814 mice exhibited a lower trend in synovitis score (Figure 2F).…”
Section: Resultsmentioning
confidence: 91%
“…Endogenous products arising from tissue senescence, which is associated with aging, may also cause maladaptive hyperactivation of this sensor, which is highly detrimental. CRISPR/Cas9 mice with a constitutively inactivated gp130 Y814 (mutation of tyrosine (Y) 814 to phenylalanine (F) – “F814” mice exhibit substantially accelerated regenerative responses (18). Both genetic and drug-mediated inactivation of SFK recruitment to gp130 receptor result in enhanced resolution of inflammation and accelerated regenerative outcomes in several injury models (18).…”
Section: Introductionmentioning
confidence: 99%